Expressive Action on Meme in Instagram Towards The Election of President and Vice President 2019 - Aziz Fauzi; Eerwin Salpa Riansi; Dwi Kurniasih (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
This study aims to classify expressive speech acts through writing and images in memes on Instagram towards PILPRES 2019, as well as analyzing the form of expressive speech acts in the writing and images of memes on Instagram towards PILPRES 2019. The method used in this research is qualitative descriptive method. The data in this study are in the form of writing in memes on Instagram. Data collection techniques in this study were carried out using literature study techniques, note taking techniques, and documentation techniques. The results showed expressive speech found in memes on Instagram towards PILPRES (Presidential Election) in 2019, the results of the research found the forms of Expressive Speech Actions (Giving Love), Expressive Speech Actions (Insulting), Expressive Speech Actions (Praising), Expressive Speech Actions (Blaming) and Expressive Actions (Mocking). In addition, language has the following functions, expressive functions, directive functions, aesthetic functions, physical functions, informational functions. This function is used to express language into memes.